Świeccy pasterze polskiego kina. Analiza porównawcza filmów „Boże Ciało” (2019) Jana Komasy i „Wszystkie nasze strachy” (2021) Łukasza Rondudy i Łukasza Gutta - Domalewski, Adam (Załącznik Kulturoznawczy, 2024)
Two recent high-profile Polish films with church themes – Corpus Christi and All Our Fears – have as their protagonists lay people who, nonetheless, due to their religious commitment, take on the role of spiritual guides in their communities. Their inner strength is grounded in a personal relationship with God, yet they remain on a collision course with the institution and teachings of the Church. Corpus Christ tells the story of a false priest, Daniel, who seeks to relieve the local community of its anger and pain after a tragic car accident. In All Our Fear, we follow a young artist who tries to live openly as a homosexual person, while also being a member of the Roman Catholic Church community. Daniel (both characters bear the same name) similarly tries to relieve the pain and grief of the local community following the suicide of a young lesbian girl. Both films, inspired by true events, are not limited to simple criticism of the Church, which sets them apart from others dealing with the subject of faith and the Church in recent Polish cinema. In this article, I conduct a comparative analysis of the two films, discussing the role of religious rituals (a Catholic burial and the Stations of the Cross service, respectively), prayer, sexuality and violence in both works. Despite many plot similarities, the pictures differ significantly in the way they portray their protagonists. Daniel's fate in Komasa's Corpus Christi is tragic, and the film employs numerous biblical “hermeneutic transpositions”, which allows it to be considered an example of post-secular cinema. In All Our Fears, Daniel Rycharski is an artist who reworks his experiences into an art form. The film thus reveals its elegiac and therapeutic nature – Daniel's works are intended to commemorate the deaths of people persecuted because of their sexual orientation. However, it is difficult to speak of inner transformation of the protagonist in this case. Instead, the film tries to idealize him: All Our Fears is a biography of Daniel Rycharski filmed to appreciate his “ecumenical” attitude, which is treated here as a moral model. Gutt and Ronduda's film can be described as strongly persuasive, and in some aspects even tendentious – the filmmakers portray Daniel in an (almost) hagiographic manner.